Profil dan Kinerja Usaha Olahan Perikanan di Kelurahan Sarijaya Kecamatan Sanga Sanga Kabupaten Kutai Kartanegara - Haqiqiansyah, Gusti; Sugiharto, Eko (Jurnal Pertanian Terpadu, 2021)
Fishery product processing business was an effort to increase and add value to fishery products. Activities that involve the community, especially womens who have the potential to be empowered. Fishery product processing activities, especially amplang processing in Sari Jaya Village, Sanga Sanga District, has been developing for a long time. Research aimed was to determine the business profile and business performance financially and to determine the breakeven point of production. The research was conducted using survey methods and interviews with business actors. The sample was taken by using the census method and the data were analyzed descriptively and financially. The research results showed that the business profile was household scale, simple technology, family labour and it has a business license (P-IRT). Financial analysis results showed that the balance value of revenue and costs was 2.19, it means by financially this business is profitable and prospects to be developed. Analysis results of break-even point production were 118 kg per month, while an average production actual is 258 kg per month. While the actual average production was 258 kg per month. The break-even point price is at level of Rp. 45,697 per kg. As for advice, intensive assistance required by technical agencies, especially field extension workers so that they can improve the quality of production and partnership programs to expand market segmentation.